2018
DOI: 10.5430/ijhe.v7n6p63
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Motivation and Self-Efficacy on Math Studies in the Israeli Ministry of Education's Program "Give Five"

Abstract: Studying mathematics is an essential condition for acquiring an education in most fields such as all exact sciences, financial sphere, programming, etc. It enables students to choose from among a large variety of professions with significantly high chances of academic admission, mainly in fields such as engineering, natural sciences, and technology, as well as in a considerable part of the social sciences Hence, studying mathematics in high school is a critical and key factor for continued studies and for inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…In a meta-analytic review of studies, males were found to have a higher MSE than their female counterparts (Huang, 2013). On the contrary, no gender differences in MSE were observed in other studies (Ayotola and Adedeji, 2009;Clutts, 2010;Turgut, 2013;Davidovitch and Yavich, 2018;Probst, 2019).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…In a meta-analytic review of studies, males were found to have a higher MSE than their female counterparts (Huang, 2013). On the contrary, no gender differences in MSE were observed in other studies (Ayotola and Adedeji, 2009;Clutts, 2010;Turgut, 2013;Davidovitch and Yavich, 2018;Probst, 2019).…”
Section: Introductionmentioning
confidence: 85%
“…Mathematics is a prerequisite for pursuing higher education in most professions, including all exact sciences, finance, programming, and so on. It allows students to choose from a wide range of vocations with high prospects of academic acceptance, mostly in engineering, the natural sciences, and technology, as well as a significant portion of the social sciences (Davidovitch and Yavich, 2018). This calls for a closer look at teaching and learning of mathematics.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Bringula et al (2021) showed that there is a positive correlation between mathematics learning autonomy and various academic outcomes, including achieving high grades, proficient problem-solving, ease in completing assignments, effective lesson recall, and outperforming peers or fellow students. Self-reliant learners were more motivated in their mathematics learning, resulting in greater success results (Davidovitch & Yavich, 2018).…”
Section: Introductionmentioning
confidence: 99%